1997
DOI: 10.1056/nejm199702203360801
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Digoxin on Mortality and Morbidity in Patients with Heart Failure

Abstract: Digoxin did not reduce overall mortality, but it reduced the rate of hospitalization both overall and for worsening heart failure. These findings define more precisely the role of digoxin in the management of chronic heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
273
2
9

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,596 publications
(288 citation statements)
references
References 10 publications
4
273
2
9
Order By: Relevance
“…Nevertheless, this study is based on the largest randomized controlled trial in patients with AF. Finally, the association between digoxin and worse clinical outcomes as demonstrated in the current analysis was not demonstrated in the only prospective trial with digoxin in patients with HF 29. However, this trial was limited to patients in sinus rhythm, and no conclusions can be made with regards to patients with AF.…”
Section: Discussionmentioning
confidence: 58%
“…Nevertheless, this study is based on the largest randomized controlled trial in patients with AF. Finally, the association between digoxin and worse clinical outcomes as demonstrated in the current analysis was not demonstrated in the only prospective trial with digoxin in patients with HF 29. However, this trial was limited to patients in sinus rhythm, and no conclusions can be made with regards to patients with AF.…”
Section: Discussionmentioning
confidence: 58%
“…Based on the energetic consequences of calcium handling by the myocyte in an experimental animal model, a beneficial effect of digitalis in CHF may depend upon the stage of disease 37. In humans, digoxin did not decrease overall mortality in a large trial of human CHF patients, but did decrease the rate of hospitalization and worsening CHF 38. However, in a meta‐analysis of digoxin use and mortality risk in humans with AF, digoxin use was associated with a greater risk for mortality regardless of concomitant CHF 39.…”
Section: Discussionmentioning
confidence: 99%
“…First, an analysis showed that digoxin was prescribed at the time of hospital discharge to a greater extent for patients with BpEF and pEF who died. Definitive evidence for digoxin efficacy in HF comes from the Digitalis Investigation Group's randomized clinical trial, which showed that although this medication does not improve survival, it appears to be associated with a reduced risk of hospitalization 30. The second observation was that patients from all 3 EF strata who were still alive 1 year after hospital discharge were treated with multiple cardiac medications at the time of hospital discharge.…”
Section: Discussionmentioning
confidence: 99%